2015
DOI: 10.1002/cyto.b.21318
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of receptor occupancy data: A valuable technology for biotherapeutic drug development

Abstract: Background: In drug development, in vivo assessment of target engagement provides confidence when testing the drug's mechanism of action and improves the likelihood of clinical success. For biologics, receptor occupancy (RO) determined from circulating cells can provide evidence of target engagement. Integrating this information with mathematical modeling can further enhance the understanding of drugtarget interactions and the biological factors that are critical to the successful modulation of the target and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The K D of the antibody to the cell receptor is estimated by fitting MFI as a function of the antibody concentration. Integrating receptor occupancy data using mathematical models can provide a means of testing hypotheses, as well as providing a basis for extrapolation of preclinical findings to humans [29].…”
Section: In Vitro Evaluations Of Monoclonal Antibody Bindingmentioning
confidence: 99%
“…The K D of the antibody to the cell receptor is estimated by fitting MFI as a function of the antibody concentration. Integrating receptor occupancy data using mathematical models can provide a means of testing hypotheses, as well as providing a basis for extrapolation of preclinical findings to humans [29].…”
Section: In Vitro Evaluations Of Monoclonal Antibody Bindingmentioning
confidence: 99%
“…Since the original model was published, a myriad of examples have been reported, showcasing state-of-the-art mathematical models of mAbs exhibiting TMDD. 26 Meijer et al 27 showed that T cell depletion by modulation of their CD3 surface antigens with an anti-CD3 antibody results in a decreased clearance of the mAb at subsequent doses. Ng et al 28 described the PK of TRX1, an anti-CD4 mAb, simultaneously modeling the time-course profiles of free drug exposure and free and total CD4 in healthy subjects.…”
Section: Monoclonal Antibody Dispositionmentioning
confidence: 99%
“…These measurements are particularly important given the prevalence of anti‐drug antibodies in xenogeneic species (Thway et al, 2013). When used as a pharmacodynamic (PD) measurement, ROA data may be combined with pharmacokinetic (PK) data for modeling in order to optimize clinical trial design, guide dose selection, and determine the duration and extent of target saturation (Fisher et al, 2016; Quadrini et al, 2016; Spilker, Singh, & Vicini, 2016; Sternebring et al, 2016; Wyant, Estevam, Yang, & Rosario, 2016). When integrated with anti‐drug‐antibody (ADA) results, ROA data are used to assess the impact of ADA on receptor engagement and to monitor the association of long‐term receptor binding with adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…clinical trial design, guide dose selection, and determine the duration and extent of target saturation (Fisher et al, 2016;Quadrini et al, 2016;Spilker, Singh, & Vicini, 2016;Sternebring et al, 2016;Wyant, Estevam, Yang, & Rosario, 2016). When integrated with anti-drugantibody (ADA) results, ROA data are used to assess the impact of ADA on receptor engagement and to monitor the association of longterm receptor binding with adverse events.…”
mentioning
confidence: 99%